Night fall [large type] - Mehl, Nancy (Mehl, Nancy. Quantico files ;, 2022)
"Finally free of her troubled upbringing, Alex Donovan is able to live out her childhood dream of working for the FBI. But soon after she becomes a member of the FBI's elite Behavioral Analysis Unit, authorities in Missouri contact them about bodies found on freight trains - all killed in the same way. Alex never expected to be forced to confront her past in this new job, but she immediately recognizes the graffiti messages the killer is leaving on the train cars. When the BAU sends her to gather information about the messages from her aunt in Wichita, Kansas, Alex is haunted by the struggles she thought she'd left behind forever. In a race against time to solve the case and recover a deadly virus sample the killer intends to spread, Alex must face how far she'll go - and what she's willing to risk - to put a stop to the Train Man."--